Antiphospholipid Syndrome and the Neurologist: From Pathogenesis to Therapy - Fleetwood, Thomas; Cantello, Roberto; Comi, Cristoforo (Frontiers in Neurology, 2018)
Antiphospholipid syndrome (APS) is an autoimmune antibody-mediated condition characterized by thrombotic events and/or pregnancy morbidity in association with persistent positivity to antiphospholipid antibodies (aPL). The nervous system is frequently affected, as intracranial vessels are the most frequent site of arterial pathology. Over the course of years, many other neurological conditions not included in the diagnostic criteria, have been associated with APS. The pathogenic mechanisms behind the syndrome are complex and not fully elucidated. aPL enhance thrombosis, interfering with different pathways. Nevertheless, ischemic injury is not always sufficient to explain clinical features of the syndrome and immune-mediated damage has been advocated. This may be particularly relevant in the context of neurological complications. The reason why only a subgroup of patients develop non-criteria nervous system disorders and what determines the clinical phenotype are questions that remain open. The double nature, thrombotic and immunologic, of APS is also reflected by therapeutic strategies. In this review we summarize known neurological manifestations of APS, revisiting pathogenesis and current treatment options.